Long-Term Effectiveness of Intensive Blood Pressure Management Led by Nonphysician Community Healthcare Providers on Cardiovascular Events: 7-Year Follow-Up of a Cluster Randomized Trial - Guozhe Sun; Xiaofan Guo; Chuansheng Zhao; Nanxiang Ouyang; Guangxiao Li; Chang Wang; Yuan Ren; Liying Xing; Zhaoqing Sun; Lixia Qiao; Shanshan Zhong; Songyue Liu; et al. (Circulation, 2026)
BACKGROUND: Hypertension is the leading risk factor for cardiovascular disease (CVD) worldwide. Implementation-based blood pressure (BP) control programs improve BP control and reduce CVD risk, but whether their benefits persist after withdrawal of trial-supported intervention components remains uncertain, especially when intensive BP control is targeted. In CRHCP (China Rural Hypertension Control Project), a nonphysician community healthcare provider (NPCHP)–led program with the intensive target of